Evaluación de los puestos de trabajo del centro de mantenimiento aeronáutico diafcema y su incidencia en la gestión del talento humano en el período 2015-2016 - Reyes Villavicencio, Néstor Danilo (2016)
The present study was aimed at evaluating the jobs in the company DIAF-CEMA in the province of Cotopaxi, to develop a Technical and Administrative document that helps the department Management Talent task of risk mitigation and selection personnel for each job. In this way the department can provide a suitable environment and exploit the full potential of every worker, contributing to increase the efficiency and productivity of the organization. In the research process each of the jobs analyzed, with the risk matrix, the functions manual, the survey and interviews that allowed the collection of information, to later to raise an aid proposal, The study was raised a non- experimental investigation and adopted a form field, applying tools such as observation and document review to evaluate the jobs of the company DIAF-CEMA, and with the results obtained was identified factors and important elements of each of them….